Final height in Italian patients with congenital hypothyroidism detected by neonatal screening: a 20-year observational study. Issue 1 (December 2015) - Delvecchio, Maurizio; Vigone, Maria; Wasniewska, Malgorzata; Weber, Giovanna; Lapolla, Rosa; Popolo, Pietro; Tronconi, Giulia; Di Mase, Raffaella; De Luca, Filippo; Cavallo, Luciano; Salerno, Mariacarolina; Faienza, Maria
Abstract Background Linear growth and final height are reported as normal in congenital hypothyroid patients in the neonatal screening era. Methods We evaluated the final height in 215 patients with congenital hypothyroidism to assess if it improved over the last 2 decades. Results Final height (-0.1 ± 1.0 SDS) was higher than target height (-0.8 ± 1.0 SDS, p  < 0.001) and not different among the 4 quartiles for birthdate. It was correlated with target height (r2  = 0.564, p  < 0.001) and height at puberty onset (r2  = 0.685, p  < 0.001), but not with age at diagnosis or the starting LT4/kg/day dose. The curve fitting analysis showed that the age at diagnosis progressively decreased during the 20-year study period, while the target height and the starting LT4/kg/day increased. Final height was not affected by the birthdate, the age at diagnosis, the starting LT4 dose. Conclusions The final height is higher than the target height, but despite the improvement in the screening and the treatment, it did not improve over the last 20 years. These findings are in keeping with the described secular trend and suggest that earlier diagnosis and replacement therapy do not significantly modify final height in these patients.